Processing method for reducing forming load of rare earth magnesium alloy
By using a variable-strain rate method of combining the strain rate from low to high or high to low in magnesium alloys, and combined with heat treatment, the problem of excessive molding load at high strain rate of magnesium alloys is solved, and the rare earth magnesium alloys are realized efficient machining and mechanical performance improvement.
Patent Information
- Application Number
- CN202411507375.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-27
AI Technical Summary
The molding load of magnesium alloys at high strain rates is too large, resulting in increased processing difficulty, low production efficiency and high cost, which limits the widespread application of magnesium alloy products.
The thermal compression deformation is carried out using a variable strain rate combination from low to high or high to low. The molding load of rare earth magnesium alloy is reduced through preheating and phased strain rate adjustment, and combined with solid solution and aging heat treatment to improve mechanical properties. .
It effectively reduces the molding load of rare earth magnesium alloys, improves production efficiency, broadens the application range of magnesium alloys in wide-scale and large-deformed profile processing, and improves the mechanical properties of the alloys.
Smart Images

Figure CN119194314A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic deformation processing of rare earth magnesium alloys, and in particular relates to a processing method for reducing the forming load of rare earth magnesium alloys. Background Art
[0002] With the development of human society and the progress of science and technology, energy shortage and environmental pollution have become the focus of modern economic development and social progress. The large-scale application and promotion of lightweight components is a global development trend, which is of great significance for alleviating energy crisis, improving environmental pollution and improving economic benefits. As the lightest metal structural material, magnesium alloy has received great attention in the fields of automobile, rail transit, aerospace, electronics 3C, etc. due to its high specific strength, good damping characteristics and good processability. As the lightest metal structural material, magnesium alloy can further reduce energy consumption by replacing aluminum alloy in the bottom plate profile of rail transit trains.
[0003] However, the absolute strength of magnesium and magnesium alloys is relatively low, and the plasticity is poor, which seriously restricts their wide application in structural materials. In order to improve the strength and plasticity of magnesium alloys, a series of alloying elements are usually added. The addition of rare earth elements (Gd, Y and Nd, etc.) can effectively improve the internal microstructure and structure of the alloy, greatly improving the strength of magnesium alloys at room temperature and high temperature.
[0004] In recent years, Mg-Zn-RE deformable magnesium alloys have been widely studied and paid attention to due to their high room temperature and high temperature strength, as well as excellent creep resistance. However, magnesium and magnesium alloys have a close-packed hexagonal structure, with fewer independently activated slip systems and poor room temperature formability. Temperature and strain rate are two important parameters in the forming process of magnesium alloys. Increasing the temperature can effectively reduce the critical partial shear force, activate other slip systems, improve the formability of magnesium alloys and reduce the deformation load during the forming process. In order to reduce the forming load and improve the formability of magnesium alloys, the deformation temperature is usually above 380°C; deformation at high strain rates requires higher deformation loads and is prone to increase the risk of cracking during processing, which will be higher than 1s -1 There are still some difficulties in applying the strain rate to the plastic deformation process of magnesium alloys.
[0005] At present, the processing of magnesium alloys is still mainly based on deformation at high temperature and low strain rate. The lower strain rate will lead to lower production efficiency and increase production costs, which to a certain extent limits the processing and application of magnesium alloy products. At the same time, in the actual extrusion processing and production process, due to the high strength and hardness of rare earth magnesium alloys themselves, the addition of too many rare earth elements leads to a narrowing of the deformation processing window. For large deformation profiles, there are still great challenges even when deforming at a relatively high strain rate at high temperature. The extrusion forming load will rise sharply at a high strain rate, which is difficult to meet with existing equipment, increasing the difficulty of forming. Therefore, finding a processing technology for magnesium alloys under high strain rate deformation and reducing the load during high strain rate deformation is of vital significance to broaden the practical application of magnesium alloys and solve the forming problems faced in the processing of wide and large deformation profiles. Summary of the invention
[0006] In view of the excessive forming load of the wide and large-sized magnesium alloy with high rare earth content, the purpose of the present invention is to provide a processing method for reducing the forming load of the rare earth magnesium alloy. The processing method provided by the present invention, during plastic deformation, first forms at a low strain rate and then suddenly increases the strain rate, and reduces the forming load during the thermal deformation of the rare earth magnesium alloy by changing the deformation loading rate, while achieving controllability of production efficiency.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention discloses a processing method for reducing the forming load of rare earth magnesium alloy, wherein the rare earth magnesium alloy material is preheated and then heated for 0.001s. -1 -10s -1 Within the range of strain rate, a variable strain rate method of transitioning from low to high strain rate or combining high and low strain rates is adopted to perform hot compression deformation until the deformation amount is 30-60%.
[0009] The process of the present invention can effectively reduce the forming load by adopting a processing technology of transitioning the strain rate from low to high or combining high and low strain rates during the plastic deformation process.
[0010] The present invention discloses a processing method for reducing the forming load of rare earth magnesium alloy, wherein the rare earth magnesium alloy material is preheated, and then heated for 0.1s -1 -1s -1 The first stage of hot compression deformation is carried out at a strain rate of 1s until the deformation is 10%-20%, and then the strain rate is immediately increased to 1s while maintaining the load. -1 -10s -1 The second stage of hot compression deformation is carried out until the deformation amount is 40-45%, wherein the strain rate of the second stage of hot compression deformation is 5-10 times the strain rate of the first stage of hot compression deformation.
[0011] The inventors found that when the strain rate is increased under a constant strain rate, the corresponding deformation load increases; and under a variable strain rate, although the sudden increase in the strain rate also causes an increase in the deformation load, the peak load that can be achieved in the high strain rate stage under the variable strain rate is much lower than the peak load that can be achieved at the same strain rate under a constant strain rate. Therefore, the above method can greatly reduce the forming load of rare earth magnesium alloys, and at the same time the mechanical properties are improved.
[0012] In the processing method of the present invention, the coordination of various process parameters is also crucial. For example, the strain rate of the first stage needs to be controlled within the scope of the present invention, because the required forming load is small at a low strain rate, and the forming load will increase accordingly when the strain rate is increased. When the strain rate increases, the forming load of the second stage increases on the basis of the load of the first stage. If the strain rate in the first stage is too large, the forming load will also be high, which will lead to a higher load in the second stage. The total forming load in the entire deformation process will be high, so the effect of reducing the forming load under the variable rate is not obvious; and the deformation amount in the first stage also needs to be controlled within the above range, because the strain rate The increase requires a certain amount of time. If the deformation in the first stage is too large, the deformation left for the second stage is not enough to meet the deformation required for the increase in strain rate. That is, when the deformation is constant, the deformation in the first stage is too large, and the strain in the second stage will be too small, and the corresponding strain rate may not be reached. As the deformation increases, the stress first rises rapidly to the peak value and then slowly decreases. The stress change in the second stage changes continuously on the basis of the first stage. If the deformation in the first stage is too small, the deformation may enter the second stage just after reaching the peak value, and the stress will increase significantly. The final forming load is large, which cannot reduce the load, or the load reduction effect is not obvious.
[0013] The process of the present invention is applicable to Mg-Gd-based rare earth magnesium alloys containing rare earth elements Gd and Y, but the inventors have found that the process of the present invention has a greater impact on Mg-Gd-based rare earth magnesium alloys with the following components.
[0014] In a preferred embodiment, the rare earth magnesium alloy material has the following composition by mass percentage: Gd: 8.5-9.5%; Y: 3.4-4.5%; Zn: 1.0-1.5%; Zr: 0.4-0.7%; Cu: ≤0.02%; Ni: ≤0.005%; Fe: ≤0.01; and the balance is Mg.
[0015] In a preferred solution, the preheating temperature is 350°C-470°C, preferably 400°C-450°C, and the holding time is 3-10 minutes. The rare earth magnesium alloy material is first preheated and held to make the overall temperature distribution of the material uniform, and then hot compression deformation is performed. The inventors have found that appropriately increasing the temperature is conducive to reducing the deformation load, but the temperature should not be too high to avoid cracking.
[0016] Further preferably, the heating rate during the preheating process is 3-5 K / s.
[0017] The preferred solution is to quench after the second stage of hot compression deformation is completed, and then perform heat treatment, the heat treatment process is: first perform solid solution treatment, and then perform aging treatment, the temperature of the solid solution treatment is 470-520°C, and the time of the solid solution treatment is 10h-24h; the temperature of the aging treatment is 200-250°C, and the time of the aging treatment is 24h-48h.
[0018] Further preferably, the temperature of the solution treatment is 520° C., and the time of the solution treatment is 10-12 h; the temperature of the aging treatment is 200° C., and the time of the aging treatment is 24-36 h.
[0019] Principles and advantages
[0020] The process of the present invention adopts a processing technology of transitioning the strain rate from low to high or combining high and low strain rates to effectively reduce the forming load during the plastic deformation process.
[0021] Under constant strain rate, increasing temperature is beneficial to reducing deformation load, while increasing strain rate increases deformation load; under variable strain rate, the sudden increase of strain rate also causes an increase in deformation load. However, the peak load that can be achieved in the high strain rate stage under variable strain rate is lower than the peak load that can be achieved at the same strain rate under constant strain rate.
[0022] After heat treatment, the constant low strain rate (1s -1 ) the internal grain size of the alloy is 5.99 μm, and the constant high strain rate (10s -1 ) the internal grain size of the alloy is 6.71 μm, the strain rate (1→10s -1 ) is 6.21 μm. -1 ) the tensile strength of the alloy is 356MPa and the elongation is 1.38%; at a constant high strain rate (10s -1 ) the tensile strength of the alloy is 315MPa and the elongation is 1.65%; the strain rate (1→10s -1) The tensile strength of the alloy is 330MPa and the elongation is 1.8%. It can be seen that compared with constant high strain rate loading, variable rate loading molding improves the mechanical properties and can significantly reduce the flow stress during the molding process while retaining the same microstructure. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a two-stage variable strain rate compression loading process diagram in the present invention. The strain rate changes from slow to fast, and the single-stage strain rate remains constant. The slow strain rate range of the first stage is selected to be 0.1-1s -1 The second stage fast strain rate range is selected as 1-10s -1 .
[0024] Figure 2 In Example 2, 1s -1 Grain structure diagram after constant slow strain rate compression, the average grain size is 5.99μm.
[0025] Figure 3 In Example 2, 10s -1 Grain structure diagram after compression at a constant fast strain rate, the average grain size is 6.71μm.
[0026] Figure 4 This is the grain structure diagram after compression when the strain rate changes from slow to fast in Example 1, and the average grain size is 6.25 μm.
[0027] Figure 5 In Example 1 and Comparative Example 2, 1s -1 The constant slow strain rate is 10s in Comparative Example 2. -1 The tensile properties of the resulting material after final heat treatment were tested at a constant fast strain rate. DETAILED DESCRIPTION
[0028] The alloy used in the following examples is a commercial magnesium rare earth alloy extruded rod with the grade WE94, and the nominal chemical composition is: Gd: 9%; Y: 4%; Zn: 1%; Zr: 0.5%, and the actual chemical composition is: Gd: 8.5%; Y: 4%; Zn: 1.2%; Zr: 0.4%.
[0029] Example 1
[0030] 13 mm × 20 mm cylindrical specimens were processed from commercial extruded rods and the surface oil was removed;
[0031] The sample was placed on a thermal compression simulator for preheating and insulation at a preheating temperature of 450°C and a insulation time of 3 minutes.
[0032] After the temperature is evenly distributed, continue for 1 second -1 -10s-1 Isothermal compression test with variable strain rate.
[0033] The specific steps are as follows:
[0034] Step 1: Process a 13 mm × 20 mm cylindrical specimen from a commercial extruded bar and wipe it with anhydrous ethanol to remove the oil stain on the surface;
[0035] Step 2: The sample is placed on a thermal compression simulator for preheating and heat preservation, the preheating temperature is 450°C, and the heat preservation time is 3 minutes;
[0036] Step 3: After the temperature is evenly distributed, -1 The first stage of isothermal compression was carried out at a strain rate of 20%;
[0037] Step 4: Then, the load is maintained and the strain rate is changed from 1s to -1 Immediately changes to 10s -1 The second stage of isothermal compression was carried out with a reduction of 20%;
[0038] Step 5: After the total reduction reaches 40%, the compression is stopped, and the load is immediately quenched after unloading to retain the internal deformation structure and obtain the stress-strain curve;
[0039] Step 6: Take a small-sized sample from the compressed sample and perform a tensile property test according to the preferred heat treatment system (first perform a solution treatment at a temperature of 520°C and a solution treatment time of 12 h; then perform an aging treatment at a temperature of 200°C and a aging treatment time of 32 h.
[0040] The peak stress during the deformation of this embodiment is 139 MPa, which is higher than that of the constant stress of 10 s. -1 The peak stress during deformation is reduced by 24.9%, providing an alloy with a tensile strength of 330 MPa and an elongation of 1.8%.
[0041] Example 2
[0042] The raw material used is extruded commercial WE94 magnesium alloy, and the actual composition of the alloy is: Gd: 8.5%; Y: 4%; Zn: 1.2%; Zr: 0.4%.
[0043] 13 mm × 20 mm cylindrical specimens were processed from commercial extruded rods and the surface oil was removed;
[0044] The sample was placed on a thermal compression simulator for preheating and insulation at a preheating temperature of 450°C and a insulation time of 3 minutes.
[0045] After the temperature is evenly distributed, continue for 1 second -1 -5s -1 Isothermal compression test with variable strain rate.
[0046] The specific steps are as follows:
[0047] Step 1: Process a 13 mm × 20 mm cylindrical specimen from a commercial extruded bar and wipe it with anhydrous ethanol to remove the oil stain on the surface;
[0048] Step 2: The sample is placed on a thermal compression simulator for preheating and heat preservation, the preheating temperature is 450°C, and the heat preservation time is 3 minutes;
[0049] Step 3: After the temperature is evenly distributed, -1 The first stage of isothermal compression was carried out at a strain rate of 20%;
[0050] Step 4: Then, the load is maintained and the strain rate is changed from 1s to -1 Immediately change to 5s -1 The second stage of isothermal compression was carried out with a reduction of 20%;
[0051] Step 5: After the total reduction reaches 40%, the compression is stopped, and the load is unloaded and immediately water quenched to obtain the stress-strain curve.
[0052] Step 6: Take a small-sized sample from the compressed sample, and perform a tensile property test after heat treatment according to the optimal heat treatment system.
[0053] The peak stress during the deformation of this embodiment is 129 MPa, and the constant rate is 5 s -1 The peak stress is 163MPa, and the change rate is 5s -1 Compared with the constant rate of 5s -1 The peak stress is reduced by 21%, and the alloy provided has a tensile strength of 338 MPa and an elongation of 1.6%.
[0054] Example 3
[0055] The raw material used is extruded commercial WE94 magnesium alloy, and the actual composition of the alloy is: Gd: 8.5%; Y: 4%; Zn: 1.2%; Zr: 0.4%.
[0056] 13 mm × 20 mm cylindrical specimens were processed from commercial extruded rods and the surface oil was removed;
[0057] The sample was placed on a thermal compression simulator for preheating and insulation at a preheating temperature of 450°C and a insulation time of 3 minutes.
[0058] After the temperature is evenly distributed, continue for 0.1s -1 -1s -1 Isothermal compression test with variable strain rate.
[0059] The specific steps are as follows:
[0060] Step 1: Process a 13 mm × 20 mm cylindrical specimen from a commercial extruded bar and wipe it with anhydrous ethanol to remove the oil stain on the surface;
[0061] Step 2: The sample is placed on a thermal compression simulator for preheating and heat preservation, the preheating temperature is 450°C, and the heat preservation time is 3 minutes;
[0062] Step 3: After the temperature is evenly distributed, -1 The first stage of isothermal compression was carried out at a strain rate of 20%;
[0063] Step 4: Then, the load is maintained and the strain rate is increased from 0.1s -1 Immediately changes to 1s -1 The second stage of isothermal compression was carried out with a reduction of 20%;
[0064] Step 5: After the total reduction reaches 40%, the compression is stopped, and the load is unloaded and immediately water quenched to obtain the stress-strain curve.
[0065] Step 6: Take a small-sized sample from the compressed sample, and perform a tensile property test after heat treatment according to the optimal heat treatment system.
[0066] The peak stress during deformation of this embodiment is 112 MPa, which is higher than that of the constant rate of 1s -1 The peak stress during deformation at a strain rate of 23% is reduced, providing the alloy with a tensile strength of 342 MPa and an elongation of 1.4%.
[0067] Comparative Example 1
[0068] The other conditions were the same as those in Example 1, and isothermal compression deformation was performed at a constant strain rate at 350° C., 400° C., and 450° C., respectively.
[0069] Comparative Example 2
[0070] The other conditions were the same as those in Example 1. The temperature was set at 450°C for 0.01, 1, and 10 s. -1 Isothermal compression deformation at a constant strain rate.
[0071] Performance Test Results
[0072] The flow stress peak values when deformed under different conditions of Comparative Examples 1 and 2 and Example 1 are shown in Table 1. It can be seen that when deforming under constant strain rate conditions, increasing the temperature is conducive to reducing the deformation load, while increasing the strain rate increases the deformation load; when deforming under variable strain rate conditions, the sudden increase in strain rate also causes an increase in deformation load. However, the peak load reached in the high strain rate stage of variable strain rate is lower than the peak load that can be achieved at the same strain rate under constant strain rate. The peak loads in Examples 1, 2, and 3 are all reduced by more than 20% compared to those under constant strain rate.
[0073] In addition, the samples heat treated under the corresponding conditions in Example 1 and the comparative example were subjected to tissue characterization and tensile testing. Figure 2-Figure 4 It can be seen that in the comparative example, the constant strain rate is 1s -1 After deformation, the internal grain size of the alloy is 5.99μm; constant strain rate 10s -1 After deformation at a constant strain rate of 1s, the grain size inside the alloy is 6.71μm; the grain size after deformation at a variable strain rate is 6.21μm. -1 The tensile strength of the alloy under the condition of constant strain rate of 10s is 356MPa and the elongation is 1.38%. -1 The tensile strength of the alloy under the strain rate is 315MPa, and the elongation is 1.65%; the tensile strength of the alloy under the variable strain rate is 330MPa, and the elongation is 1.8%.
[0074] It can be seen that when deforming under variable rate conditions, the mechanical properties of the alloy can be improved while the forming load is reduced to a great extent.
[0075] Table 1 Flow stress peak values of Example 1 and Comparative Examples 1-2 under different deformation conditions
[0076]
Claims
1. A processing method for reducing the forming load of rare earth magnesium alloy, characterized in that: The rare earth magnesium alloy material is preheated and then -1 -10s -1 Within the range of strain rate, a variable strain rate method of transitioning from low to high strain rate or combining high and low strain rates is adopted to perform hot compression deformation until the deformation amount is 30-60%.
2. A processing method for reducing the forming load of rare earth magnesium alloy according to claim 1, characterized in that: Preheat the rare earth magnesium alloy material, and then -1 -1s -1 The first stage of hot compression deformation is carried out at a strain rate of 1s until the deformation is 10%-20%, and then the strain rate is immediately increased to 1s while maintaining the load. -1 -10s -1 The second stage of hot compression deformation is carried out until the deformation amount is 40-45%, wherein the strain rate of the second stage of hot compression deformation is 5-10 times the strain rate of the first stage of hot compression deformation.
3. A processing method for reducing the forming load of rare earth magnesium alloy according to claim 1 or 2, characterized in that: The rare earth magnesium alloy material has the following components in percentage by mass: Gd: 8.5-9.5%; Y: 3.4-4.5%; Zn: 1.0-1.5%; Zr: 0.4-0.7%; Cu: ≤0.02%; Ni: ≤0.005%; Fe: ≤0.01; and the balance is Mg.
4. A processing method for reducing the forming load of rare earth magnesium alloy according to claim 1 or 2, characterized in that: The preheating temperature is 350° C.-470° C., and the insulation time is 3-10 minutes.
5. A processing method for reducing the forming load of rare earth magnesium alloy according to claim 3, characterized in that: The heating rate during the preheating process is 3-5 K / s.
6. A processing method for reducing the forming load of rare earth magnesium alloy according to claim 1 or 2, characterized in that: After the second stage of hot compression deformation is completed, quenching is performed, and then heat treatment is performed. The heat treatment process is: first solution treatment is performed, and then aging treatment is performed. The temperature of the solution treatment is 470-520°C, and the time of the solution treatment is 10h-24h; the temperature of the aging treatment is 200-250°C, and the time of the aging treatment is 24h-48h.
7. A processing method for reducing the forming load of rare earth magnesium alloy according to claim 6, characterized in that: The temperature of the solution treatment is 520° C., and the time of the solution treatment is 10-12 hours; the temperature of the aging treatment is 200° C., and the time of the aging treatment is 24-36 hours.
